Albumin: A Maverick or a Placebo? Study of Association of Serum Albumin and Albumin Therapy with Mortality in Sepsis - Shardha, Arvind Kumar; Ghosh, Labani Mrinal; Al Abdul Salam, Asma Nasser; Al Maktoumi, Talib Al Mohammed; Bai, Rekha (Advances in Social Sciences Research Journal, 2025)
Objectives: The study explores the relationship between serum albumin levels, heterogeneous (human-derived) albumin administration, and clinical outcomes in patients with sepsis. The aim is to ascertain whether Serum albumin levels can be a reliable surrogate for qSOFA in assessing mortality in patients with sepsis and whether systemic administration of Human albumin in those with serum levels <30 g/L has an impact on mortality. Methods: This retrospective study was conducted at Sohar Hospital in Oman and involved a random sample of 57 patients. The patients were initially categorized into three groups based on their predicted mortality risk using the qSOFA score: low, moderate, and high risk. The same sample was further divided into two groups according to serum albumin levels: ≥30 g/L and <30 g/L. Additionally, the patients were stratified based on whether or not they received human albumin administration. Results: Analysis revealed a non-significant trend toward better outcomes in patients with higher serum albumin levels (p = 0.097). Notably, patients with higher albumin levels experienced less clinical deterioration, whereas those with lower levels were more likely to worsen. In terms of heterogeneous (human-derived) albumin administration, results show no statistically significant association between human albumin administration and improved clinical outcomes (p = 0.222). We also analyzed the relationship between lactate: albumin ratio and qSOFA score, which showed no significant association (p=0.1994). Conclusions: Study findings suggest that while serum albumin may have a weak correlation with patient recovery, the therapeutic benefit of albumin administration remains inconclusive. This study found a weak, non-significant relationship between serum albumin levels, albumin administration, and clinical improvement in patients. Findings also indicate that while higher serum albumin levels may offer some protection against clinical decline, they are not strongly associated with improved outcomes. Conversely, patients with low serum albumin level face a substantially higher risk of negative clinical progression. These findings highlight the need for further large-scale and controlled design research to better clarify the role of albumin in patient outcomes.